Aplicação da escala SERVQUAL para avaliação da qualidade da prestação de serviços de consultoria interna - Magalhaes, Sergio Siqueira (2013)
The main purpose of this research was to evaluate the quality in the performance of services for the internal consulting portfolio of a Brazilian mixed corporation, to identify the strengths in the performance of this service, as well as the gaps between customer s expectations and perceptions. The quality of services in the present scenario is key to gaining market share or the maintenance of any business. However, in the case of the company s internal consulting portfolio, which does not have a market reserve, in the sense of a non compulsory use, with highly demanding clients, complex demands and with a strategic benchmarking indicator, the challenge is amplified in a relevant way. The methodology used in this study has as its purpose the applied research, because this study refers to the creation of a specific instrument to capture the reality as well as the intention of solving problems (gaps). As for the means is a case study, investigating a situation confined to the scenario of the company in question with focus on the internal consulting portfolio, evaluating the quality of services of the same, in a sense of greater depth and detail. The evaluation was done through questionnaires sent to 106 customers of a total of 300. Thus, it is a quantitative and qualitative study. The data was expressed with numerical measures (quantitative) and from their analysis emerged qualitative information. The scale used in this study was the SERVQUAL through its five key dimensions for quality measuring: tangible aspects, reliability, responsiveness, assurance and empathy. The result of the study confirmed the importance of the evaluation process by the customer s part to provide performance feedback, thus facilitating the entire deployment of actions for process improvement, as well as of the knowledge of the strengths of performance